Defect-engineered three-dimensional vanadium diselenide microflowers/nanosheets on carbon cloth by chemical vapor deposition for high-performance hydrogen evolution reaction. (13th April 2021) - Miao, Chengcheng; Zhang, Ting; Li, Fulin; Zhang, Lei; Sun, Jiamin; Liu, Dong; Wu, Liqian; Wang, Hang; Chen, Fenghua; He, Longbing; Han, Ning; Ma, Yandong; et al.
Abstract: In the past decades, defect engineering has become an effective strategy to significantly improve the hydrogen evolution reaction (HER) efficiency of electrocatalysts. In this work, a facile chemical vapor deposition (CVD) method is firstly adopted to demonstrate defect engineering in high-efficiency HER electrocatalysts of vanadium diselenide nanostructures. For practical applications, the conductive substrate of carbon cloth (CC) is selected as the growth substrate. By using a four-time CVD method, uniform three-dimensional microflowers with defect-rich small nanosheets on the surface are prepared directly on the CC substrate, displaying a stable HER performance with a low Tafel slope value of 125 mV dec −1 and low overpotential voltage of 295 mV at a current density of 10 mA cm −2 in alkaline electrolyte. Based on the results of x-ray photoelectron spectra and density functional theory calculations, the impressive HER performance originates from the Se vacancy-related active sites of small nanosheets, while the microflower/nanosheet homoepitaxy structure facilitates the carrier flow between the active sites and conductive substrate. All the results present a new route to achieve defect engineering using the facile CVD technique, and pave a novel way to prepare high-activity layered electrocatalysts directly on a conductive substrate.